How do you simplify [(3+2i)^ 3 / (-2+3i)^4] [(3+2i)3(2+3i)4]?

1 Answer
Jun 27, 2016

(3-2i)/1332i13

Explanation:

3+2i=sqrt(3^2+2^2)e^{i phi}3+2i=32+22eiϕ
-2+3i=sqrt(3^2+2^2)e^{i( phi+pi/2)}2+3i=32+22ei(ϕ+π2)

with phi = arctan(2/3)ϕ=arctan(23)

[(3+2i)^ 3 / (-2+3i)^4] =((3+2i)/(-2+3i))^3/( (-2+3i))=e^{-i (3pi)/2}/(sqrt(3^2+2^2)e^{i( phi+pi/2)})[(3+2i)3(2+3i)4]=(3+2i2+3i)3(2+3i)=ei3π232+22ei(ϕ+π2)
=1/sqrt(3^2+2^2)e^{-i(phi+2pi)} = 1/sqrt(3^2+2^2)e^{-i phi} ==132+22ei(ϕ+2π)=132+22eiϕ=
sqrt(3^2+2^2)/(3^2+2^2)e^{-i phi} = (3-2i)/1332+2232+22eiϕ=32i13